Encryption analysis of AES-Cipher Block Chaining performance in Crypto-Wall Ransomware and SDN based mitigation - Pillai, Anish; S. Vasanthi, M; Kadikar, Ruturaj; Amutha, B (International Journal of Engineering and Technology, 2018)
The arrival of affordable high speed internet and superior computing processors has given the ability to access a novel environment of opportunities and challenges at an individuals fingertips. Sectors of education, administration, business, medical and corporate have been revolutionised by this latest onset of technology. With the arrival of IoT (Internet of Things), the number of devices that are connected to the internet will be higher than ever before. Along with this increase, the diversity of threats propagating on the internet will see a comparable increase. These threats are designed in a way to alter the integrity of the data, embed itself into other programs for further propagation and also to gain monetary compensation. In recent times, the popular malware which has made headlines worldwide is ransomware. This type of malware infection uses complex encryption of user specific files and demands a ransom for retrieval of these files. Modern ransomware behaviour indicates propagation of the malware from the host victim to other computers and shared drives within its network. This paper contains in- detailed analysis of ransomware and the currents trends of this malware. The time taken for CryptoWall ransomware encryption using AES- CBC is observed for various data sizes and a SDN approach for ransomware threat mitigation is discussed.Â